Development and Testing of a Literature Search Protocol for Evidence Based Nursing: An Applied Student Learning Experience - Hickner, Andy; Friese, Christopher R.; Irwin, Margaret (Evidence Based Library and Information Practice, 2011)
Objective – The study aimed to develop a search protocol and evaluate reviewers' satisfaction with an evidence-based practice (EBP) review by embedding a library science student in the process. Methods – The student was embedded in one of four review teams overseen by a professional organization for oncology nurses (ONS). A literature search protocol was developed by the student following discussion and feedback from the review team. Organization staff provided process feedback. Reviewers from both case and control groups completed a questionnaire to assess satisfaction with the literature search phases of the review process. Results – A protocol was developed and refined for use by future review teams. The collaboration and the resulting search protocol were beneficial for both the student and the review team members. The questionnaire results did not yield statistically significant differences regarding satisfaction with the search process between case and control groups. Conclusions – Evidence-based reviewers' satisfaction with the literature searching process depends on multiple factors and it was not clear that embedding an LIS specialist in the review team improved satisfaction with the process. Future research with more respondents may elucidate specific factors that may impact reviewers' assessment.